Implementation of E-Monalisa and the Authority of the People's Welfare Section in Grants Distribution of Denpasar City - Parasari, Nyoman Sri Manik; Saputra, I Gusti Ngurah Jhon (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
On The Job Training Report examines the authority of the People's Welfare Section regarding the distribution of grants in Denpasar City and the obstacles faced in the effectiveness of E-Monalisa to support grants in the Welfare section of the Denpasar City Secretariat. This study is motivated by the phenomenon of the rapid development of Information and Telecommunications Technology (ICT) which is used to improve the quality of public services. E-Monalisa is an online-based innovation implemented to make it easier for the public to access grant funds. The results of observational studies, documentation and interviews gave the authority of the People's Welfare Section regarding grants in Denpasar City to grant grants related to religious ceremonies such as aci upakara, work memungkah, ngenteg linggih, wastra, tedung pelinggih, and others. This authority is in accordance with the Denpasar Mayor Regulation. Number 21 of 2021 concerning Procedures for Budgeting, Implementation, and Administration, Reporting and Accountability and Monitoring of Grants and Social Assistance. Constraints in the effectiveness of E-Monalisa to support the distribution of grants in the Welfare section of the Denpasar City Secretariat pay attention to the unequal knowledge of the community about the application of e-Monalisa.